Contextual Teaching and Learning-based E-Worksheet on Science Subjects for Fourth Grade Elementary Schools - Widyaningrum, Sephia; Parmiti, Desak Putu (Universitas Pendidikan Ganesha, 2024)
Lack of motivation to learn students results in them being less focused on learning and less active during the learning process, which impacts low student learning outcomes, especially in the science and science learning process. A lack of innovative teaching materials mostly causes this or tends to be monotonous. Therefore, supportive teaching materials that are attractive in form and based on appropriate learning models are needed so that students are enthusiastic about learning and can think critically. One medium that is a solution is to use CTL-based E-Worksheet. This research aims to develop a CTL-based E-Worksheet for grade 4 elementary school science content. This research is a development research type with the ADDIE model. The research subject is CTL-based E-Worksheet media on class 4 science content. Data collection uses expert test instruments and trials. The data analysis technique calculates the percentage score for validation assessments and user responses. The research results show that the development of a CTL-based E-Worksheet for grade 4 science content meets very valid criteria from the quality aspect, with a detailed score of 93.775% from media experts, 95% from learning design experts, and 94.6% from learning content experts. The results of the student response test showed an increase from the pretest results, with an average score of 34.8%, to an average score of 84.8 on the students' post-test results. Based on these results, the CTL-based E-Worksheet teaching materials that have been developed are suitable for application in learning. This research implies that it presents CTL-based E-Worksheet learning media with grade 4 science content as a solution to problems in the student learning process.